Genome-wide expression analysis of LBD genes in tomato (Solanum lycopersicum L.) under different light conditions - Limei Dong; Hakim Manghwar (Plant Signaling & Behavior, 2023)
Lateral organ boundaries (LOB) domain (LBD) genes, a gene family that encodes the transcription factors (TFs) of plants, plays crucial functions in the development and growth of plants. Currently, genome-wide studies of the LBD family are still limited to tomato (Solanum lycopersicum L.), which is considered an important economic crop. In this study, we performed a genome-wide analysis of LBD in tomato. In total, 56 LBDs were found in the tomato genome. Protein alignment and phylogenetic classification showed that LBDs were conserved with other species. Since light emitting diodes (LEDs) light have promising applications for tomato growth. To better understand the potential function of LBDs in response to LED light in tomato, we conducted a genome-wide expression analysis of LBD genes under different light conditions. As expected, different LED lights affected the tomato growth (e.g. hypocotyl length). RNA-seq data showed that eight LBDs in tomato seedlings were differentially expressed under different light treatments, including white, blue, red, and far-red light, compared to the dark-grown condition. It indicates that these LBDs might regulate plant development in different LED light conditions. Interestingly, two LBD genes (SlLBD1 and SlLBD2) were found to be differentially expressed in four distinct lights, which might be involved in regulating the plant architecture via a complicated TF network, which can be taken into consideration in further investigation.